A Development of Canva-Based Workbook Learning Media to Identify the Main Idea of Exposition Text for Grade V Students of SDN Pesantren Semarang City - Yovika Tarisarahma; Sukarir Nuryanto (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The main problem of the research, namely the ability/competence to identify the main idea of exposition text (the learning results show 57% of students have not reached the KKTP). The research objectives include 1) to know the development of Canva-based workbook learning media design to identify the main idea of exposition text for grade V students of SDN Pesantren Semarang City; 2) to know the feasibility of developing Canva-based workbook learning media design to identify the main idea of exposition text for grade V students of SDN Pesantren Semarang City; 3) to know the practicality of developing Canva-based workbook learning media design to identify the main idea of exposition text for grade V students of SDN Pesantren Kota Semarang; and 4) to know the effectiveness of developing Canva-based workbook learning media design to identify the main idea of exposition text for grade V students of SDN Pesantren Kota Semarang. The type of research is R&D with Sugiyono's method. The results of the study include 1) products with designs according to the needs of teacher and students; 2) the average product validity score of 93% means very feasible; 3) the average product practicality score of 91% means very practical; and 4) the t test results state that there is a difference in the form of an increase with an n-gain of 0.4361, meaning that the product is effective. Based on these results, the Canva-based workbook learning media developed is as needed, very feasible, very practical, and effective for learning-teaching activities and answering related problems.